Effect of Methanolic Extract of Dandelion Roots on Cancer Cell Lines and AMP-Activated Protein Kinase Pathway - Rehman, Gauhar; Hamayun, Muhammad; Iqbal, Amjad; Khan, Sumera Afzal; Khan, Hamayoon; Shehzad, Adeeb; Khan, Abdul Latif; Hussain, Anwar; Kim, Ho-Youn; Ahmad, Jamshaid; Ahmad, Ayaz; Ali, Abid; et al. (Frontiers in Pharmacology, 2017)
Ethnomedicinal knowledge of plant-derived bioactives could help us in discovering new therapeutic compounds of great potential. Certainly, dandelion has been used in traditional ethno-medicinal systems (i.e., Chinese, Arabian, Indian, and Native American) to treat different types of cancer. Though, dandelion is highly vigorous, but the potential mode of action is still unclear. In the current study, the antiproliferative activity of methanolic extracts of dandelion root (MEDr) on cell viability of HepG2, MCF7, HCT116, and normal Hs27 was investigated. It was observed that MEDr (500 μg/mL) drastically decreased the growth of HepG2 cell line, while the effect on MCF7 and HCT116 cell lines was less pronounced and no effect has been observed in Hs27 cell lines. The MEDr also enhanced the phosphorylation level of AMPK of HepG2 cells, which considered crucial in cancer treatment and other metabolic diseases. The AMPK activation by MEDr noticed in the current study has never been reported previously. The results regarding the number of apoptotic cells (HepG2 cells) were in line with the cell viability test. The current observations clearly demonstrated the potency of MEDr against liver cancer with validation that dandelion could control AMPK and thus cancer in the treated cell lines.